Closed-end Country Funds and U.S. Market Sentiment - Bodurtha, James N.; Kim, Dong-Soon; Lee, Charles M.C. (Review of Financial Studies, 1995)
Closed-end country funds can trade at large premiums and discounts from their foreign asset values (NAVs). Investigating this anomaly, we find that individual fund premiums move together, primarily because of the comovement of their stock prices with the U.S. market. Moreover, an index of country fund premiums differentiates size-ranked U.S. portfolio returns and forecasts country fund stock returns. These findings suggest that international equity prices are affected by local risk. In particular, we show that country fund premium movements reflect a U.S.-specific risk, which may be interpreted as U.S. market sentiment.